Analisis Pengaruh Bi Rate Dan Inflasi Terhadap Indeks Saham Syariah Indonesia (ISSI) Periode 2017-2020 - Sugeng, Rachmat; Sebriani, Ria; Muliana, Muliana; Syamsuddin, Syamsuddin; Abbas, Muhammad; Hadrianti, Virza (Jurnal Ilmiah Ekonomi Islam, 2024)
This study aims to determine the effect of the BI Rate and Inflation on the Indonesian Sharia Stock Index for the 2017-2020 period. This research is a quantitative research using secondary data collection methods. The statistical test used is Multiple Linear Analysis and using statistical tools (SPSS Version two one). From the results of the multiple linear regression test, it shows that simultaneously the two independent variables have a significant influence on the Indonesian Sharia Stock Index. Partially, only Inflation (X2) has a significant effect on the Indonesian Sharia Stock Index (Y), while the BI Rate (X1) does not show any effect on the Indonesian Sharia Stock Index (Y).